Identification and Stratiraphic Position of Mollusk Type Locality at West Progo Stage - Hita Pandita; Gendoet Hartono (Journal of Geoscience, Engineering, Environment, and Technology, 2019)
The location of the discovery of mollusk fossils on the island of Java is spread in various places. One location is in the Kulon Progo region known as West Progo beds. However, due to the lack of studies of mollusk fossils in the Kulon Progo region, this resulted in a lack of understanding of the location of the discovery. This study was intended to re-record the location of fossil molluscs discovery in the Kulon Progo region, with the aim of contributing to the stratigraphic arrangement in Kulon Progo. Research methods include literature studies, field investigations and laboratory analysis. The literature study includes libraries of the Dutch colonial era regarding the location of the discovery of mollusk fossils. Field studies in the form of stratigraphic measurements and sampling. Laboratory investigations include petrographic observations and identification of micro and macro fossils. The results of the investigation successfully re-identified the Kembang Sokkoh and Spolong locations which are two types of locations on the West Progo beds. Based on the lithological characteristics of the two locations included in the Jonggrangan Formation, with the Lower Miocene age based on an analysis of the fossil content of the molluscs.